2020
DOI: 10.3390/pathogens9090771
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella and Antimicrobial Resistance in Wild Rodents—True or False Threat?

Abstract: Transmission of pathogenic and resistant bacteria from wildlife to the bacterial gene pool in nature affects the ecosystem. Hence, we studied intestine content of five wild rodent species: the yellow-necked wood mouse (Apodemus flavicollis, n = 121), striped field mouse (Apodemus agrarius, n = 75), common vole (Microtus arvalis, n = 37), bank vole (Myodes glareolus, n = 3), and house mouse (Mus musculus, n = 1) to assess their potential role as an antimicrobial resistance (AMR) and Salmonella vector. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…The choice of this group of animals, collected at forest and meadow areas, was dictated by the fact that their probable contact with human settlements was occasional and therefore the animals had little contact with antimicrobials. Both the current and our previous results confirmed these assumptions [ 72 ]. Although insight into diet composition would indicate that rodents have invaded e.g.…”
Section: Discussionsupporting
confidence: 92%
“…The choice of this group of animals, collected at forest and meadow areas, was dictated by the fact that their probable contact with human settlements was occasional and therefore the animals had little contact with antimicrobials. Both the current and our previous results confirmed these assumptions [ 72 ]. Although insight into diet composition would indicate that rodents have invaded e.g.…”
Section: Discussionsupporting
confidence: 92%
“…It should be emphasized that no resistance determinants toward carbapenems were noted among the tested strains, and so far, carbapenem resistance has rarely been reported in Poland in farm animals and other wildlife species ( Lalak et al, 2016 ; Wasyl et al, 2018 ; Skarżyńska et al, 2020a , b ). However, since the first report of carbapenemase-producing Salmonella Corvallis from the migratory bird—black kite ( Milvus migrans ) in Germany ( Fischer et al, 2013 ), several new studies that presented carbapenem resistance in bacteria from free-living birds were published ( Vittecoq et al, 2017 ; Bouaziz et al, 2018 ).…”
Section: Discussionmentioning
confidence: 89%
“…Rodents-in particular rats-are well-known reservoirs of zoonotic pathogens including Salmonella [26]. Prevalence of Salmonella in rats has mainly been assessed in high-income countries and varied widely: in the natural environment, prevalence was consistently low (0 to 1%) [26,44,45] but is was higher in the proximity of human settlements (5-20%) such as cities and PLOS NEGLECTED TROPICAL DISEASES layer or pig farms (up to 28%) [29][30][31][32][46][47][48][49][50]. Of note, studies also showed a high variation in Salmonella prevalence between rats in different cities; 15% in Yokohama (Japan) versus 1% in Chicago (US), 0.34% in Nairobi (Kenya) and 0% in Baghdad (Iraq) [32,[51][52][53].…”
Section: Rats As Reservoirs Of Non-typhoidal Salmonellamentioning
confidence: 99%